Rural communities and principle of universality in pensional matters (Encuentros, 2021)
This article aims to analyze the principle of universality in pension matters for rural communities in Colombia. On the one hand, it presents a description of working conditions in the field, and on the other, an analysis of the Constitutional doctrine around the consecration of the pension as a fundamental right; Finally, the need in Colombia to tend for universal pension coverage in its rural areas is analyzed. Thus, from a qualitative research with a hermeneutical approach and the analysis of data and documentary sources (specialized literature, law, jurisprudence, DANE data), it was possible to conclude that given the conditions of poverty, informality, aging and low coverage in social protection in the countryside, our pension system must offer assurance designs appropriate to the socio-economic and living conditions of rural communities, that is, to enable a non-contributory rural pension for Colombia.